2020
DOI: 10.3390/ijerph17196969
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Narrative Versus Didactic Information Formats on Pregnant Women’s Knowledge, Risk Perception, Self-Efficacy, and Information Seeking Related to Climate Change Health Risks

Abstract: Climate change is a global threat that poses significant risks to pregnant women and to their developing fetus and newborn. Educating pregnant women about the risks to their pregnancy may improve maternal and child health outcomes. Prior research suggests that presenting health information in narrative format can be more effective than a didactic format. Hence, the purpose of this study was to test the effectiveness of two brief educational interventions in a diverse group of pregnant women (n = 151). Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 45 publications
(58 reference statements)
0
19
1
Order By: Relevance
“…While the literature is not uniform in its conclusions [ 53 , 54 ], there is evidence to suggest that narrative and perspectival persuasion can be more effective than factual–argumentative approaches [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. Research shows that audience absorption into a narrative reduces the audiences’ capacity to form counterarguments against messages contained in the narrative [ 64 , 65 , 66 ] and tends to strengthen the persuasiveness of weak arguments and appeals [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the literature is not uniform in its conclusions [ 53 , 54 ], there is evidence to suggest that narrative and perspectival persuasion can be more effective than factual–argumentative approaches [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. Research shows that audience absorption into a narrative reduces the audiences’ capacity to form counterarguments against messages contained in the narrative [ 64 , 65 , 66 ] and tends to strengthen the persuasiveness of weak arguments and appeals [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…Work in the field of public health messaging has demonstrated that messaging that focuses on narrative and rhetoric (form) tends to yield better persuasive outcomes than messaging that focuses on facts alone (i.e., content) [ 55 , 60 , 62 , 72 , 73 , 74 ]. A variety of studies from the field of advertising, media, and communication studies suggest that narrative messaging yields more effective outcomes than analytic and informative messages [ 66 , 67 , 75 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the literature is not uniform in its conclusions (Hinyard & Kreuter, 2007; Krause & Rucker, 2020), there is evidence to suggest that narrative and perspectival persuasion can be more effective than factual-argumentative approaches (Adebayo et al, 2020; Carrion, 2018; Chang, 2008; de Wit et al, 2008; Krakow et al, 2018; Kreuter et al, 2010; Murphy et al, 2013, 2015; Taylor & Thompson, 1982). Research shows that audience absorption into a narrative reduces audiences’ capacity to form counterarguments against messages contained in the narrative (Deighton & Romer, 1989; Green et al, 2004; Igartua & Barrios, 2012) and tends to strengthen the persuasiveness of weak arguments and appeals (Escalas 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Work in the field of public health messaging has demonstrated that messaging which focuses on narrative and rhetoric (form) tends to yield better persuasive outcomes than messaging which focuses on facts alone (i.e. content) (Adebayo et al, 2020; Bryan et al, 2019; Gilkey et al, 2020; Kreuter et al, 2010; Liu & Yang, 2020; Murphy et al, 2015). A variety of studies from the field of advertising, media, and communication studies suggest that narrative messaging yields more effective outcomes than analytic and informative messages (Bilandzic & Busselle, 2013; Escalas, 2006; Igartua & Barrios, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The balance of existing research tends to suggest that audiences are more likely to be persuaded by narrative approaches [ 70 , 71 , 72 , 73 ], appeals to values [ 74 , 75 , 76 ], and rhetorics of personal, lived experience [ 77 , 78 , 79 , 80 ]. Perhaps this is due to a dynamic that Maertens et al term a “broad spectrum” of persuasion [ 81 ].…”
Section: Introductionmentioning
confidence: 99%